Improvement of Overlap for 2x2 MZI Electro-Optic Switch Based on Lithium Tantalite (LiTaO3) - Sadeq Adnan Hbeeb (مجلة النهرين للعلوم الهندسية, 2022)
This research introduces a method of an electro-optic effect and electro-refractive effect that considers very imperative for high-speed optical communication systems. In this research, it presents way by a reduction the gap between the electrodes d, and this technique achieves to solve the problem of overlap for Mach-Zehnder interferometer MZI electro-optical switch base on lithium tantalite LiTaO3, also this technique suggests a model for analysis the effect parameters on the electro-optic overlap of the electro-optic switch as the ordinary positive changing of refractive index and a length of arm switch. This study achieves a better overlap by large positive changing refractive index with a suitable small length of arm about 8µm and low driving power at least 4V/µm. Also, for lithium tantalite LiTaO3, this research achieves a better performance for system using the near infrared wavelength.